Force of words: the logic of terrorist threats - Brown, Joseph M. (Columbia studies in terrorism and irregular warfare, 2020)
Terrorist groups attain notoriety through acts of violence, but threats of future violence are just as important in attaining their political goals. Force of Words is a groundbreaking examination of the role of threats in terrorist strategies. Joseph M. Brown shows how terrorists use threats, true and false, to achieve key outcomes such as social control, economic attrition, and policy concessions. Brown demonstrates that threats are integral to terrorism on a tactical level as well, distracting security forces, drawing police into traps, and warning civilians out of harm’s way when terrorists seek to limit casualties. Force of Words reorients the field of terrorism studies, prioritizing the symbolic, psychological dimension that makes this form of conflict distinctive. It expands the study of terrorist propaganda by detailing how militants tailor their threats to send the desired political message. Drawing on rich interview data, quantitative evidence, and case studies of the IRA, ETA, the Tamil Tigers, Shining Path, the Túpac Amaru Revolutionary Movement, Boko Haram, the Afghan Taliban, and ISIL, the book offers practical guidance for interpreting terrorists’ threats and assessing their credibility. Force of Words is essential reading for anyone seeking to understand the logic of terrorism.